Calculation of phenol-formaldehyde resin polycondensation process according to activity criterion - Маслош, Владимир Зиновьевич; Маслош, Ольга Владимировна; Тараненко, Наталья Николаевна; Лошкова, Елена Борисовна (Eastern-European Journal of Enterprise Technologies, 2013)
Application of the activity criterion for calculating the polycondensation process of phenol-formaldehyde resins is considered in the paper. Reactive groups, their number and structure occupy a very important place in polycondensation oligomers. The obtained formula for calculating the activity criterion is very simple and easy to use. Polycondensation constant - the molar ratio of polycondensation components, is always specified by the synthesis conditions. For determining the criterion of oligomers activity it is necessary to know the concentration of reactive groups in the oligomer. Application of the activity criterion for calculating the polycondensation process greatly facilitates determining the calculation data of polycondensation process. The calculation of activity criterion is given in the paper on the example of two phenol-formaldehyde resins − namely novolac and resole resins. Experimental data allow revealing the dependence of the degree of polycondensation oligomer polymerization on the condensation constant and activity criterion.